The Eastern enlargement of the Monetary Union: Estonia wants to move from the periphery into the centre of the Union - Alexander Zimmer; Marie McGinley (Stiftung Wissenschaft und Politik (SWP), 2006)
The year has just begun, yet in many parts of Europe, 1 January 2007 is being eagerly anticipated. This is the day when three of the new member states of the European Union, Estonia, Lithuania and Slovenia, intend to join the monetary union. Although the European Central Bank and the European Commission supported this step up until the end of last year, more and more critical voices in these institutions are now speaking of a 'premature' accession. At the centre of the criticism is the level of inflation, which is to some extent still too high and the fact that the candidate states still need to catch up economically. The debate, however, completely neglects the political signals and economic impetus which would be sent by an Eastern enlargement of the euro area. Up until now, new economic insights and economic-political developments have played an insufficient role in the evaluation of the candidate states. Estonia has long been considered by experts as a favourite for the first round of the enlargement of the euro area. Taking this country as an example, this paper shall show that the decision to be made on accession to the monetary union is neither trivial nor insignificant for the future and further development of Europe and the European integration process. (SWP-Comments / SWP)
Keywords: 320